Reticulocyte haemoglobin content in the differential diagnosis of iron deficiency anaemia and thalassemia traits in pregnancy - Islam, Nayla; Paul, Debatosh; Karim , Rezaul; Rahman, Towhidur; Rifat, Sumaia (Bangabandhu Sheikh Mujib Medical University Journal, 2024)
Background: Iron deficiency anaemia (IDA) and thalassemia traits are the common conditions of microcytic hypochromic anaemia in pregnant women. However, the laboratory tests to differentiate them are expensive. The reticulocyte haemoglobin (Ret-Hb) test is relatively cheap. This study aimed to assess whether Ret-Hb can differentiate IDA from thalassemia traits in pregnant patients. Method: This cross-sectional study was conducted in the Bangabandhu Sheikh Mujib Medical University (BSMMU) from March 2023 to February 2024. We recruited pregnant women aged 18 to 40 through antenatal visits in the Obstetrics and Gynecology Department. Microcytic hypochromic anaemia was diagnosed by complete blood counts, IDA by iron profile and thalassemia traits by haemoglobin electrophoresis. Ret-Hb was measured using the flow cytometric method. Ninety pregnant women—30 each with IDA, thalassemia traits and healthy individuals—were enrolled. Result: The mean age was 27 years. The IDA patients had significantly (P<0.001) lower levels of Ret-Hb (mean 18.1, standard deviation 3.2 pg) compared to thalassemia traits (20.8, 2.2 pg) and healthy pregnant women (29.2, 1.9 pg). Using a Ret-Hb cut-off point of 19 pg, the test had 86.7% sensitivity and 53.3% specificity to differentiate thalassemia traits from IDA. Conclusion: Ret-Hb could be considered a diagnostic test to differentiate thalassemia traits from IDA in clinical settings before expensive confirmatory tests are performed.